Irrigation wheat production constraints and opportunities in South Africa - Dube, Ernest; Tsilo, Toi J.; Sosibo, Nondumiso Z.; Fanadzo, Morris (South African Journal of Science, 2020)
South Africa currently faces a wheat production crisis, suggesting that current policies, research and development projects may not be well aligned to farmer priorities. Through exploratory research, which included field inspections and farmer and researcher interviews, we identified the major constraints to irrigation wheat yield and explored opportunities for improving the yield and farmer profits. The dominant constraint to yield was identified as the low market price for grain, which makes farmers reluctant to invest in inputs for increasing wheat yield. Poor cultivar choice, cereal-based monocropping, the high cost of irrigation, inadequate irrigation water, low crop stands, soil acidity, no-till practices and red-billed quelea (Quelea quelea) birds are negatively impacting yields. Most importantly, we highlight a misalignment between current research efforts and farmer priorities. Recommendations for corrective measures necessary to improve yield and farmer profits are provided. This new knowledge will be useful to policymakers and researchers for better orienting investments in research and development projects aimed at addressing the current wheat production crisis in the country. Significance: We highlight a misalignment between current research efforts and farmer priorities in the wheat sector, and provide new knowledge for better orienting investments in research and development projects aimed at addressing the current wheat production crisis.